Studi Atas Biaya Pemeliharaan Aktiva Tetap dan Dampaknya Pada Kelancaran Produksi UD Mekar Jaya - Micoriza, M. (Jurnal sosial dan sains, 2025)
The advancement of industrial technology has driven companies like UD Mekar Jaya (a woodworking industry) to adopt modern machinery to enhance product quality. Optimal machine maintenance is crucial for production efficiency and cost control. However, the primary constraint lies in actual maintenance costs exceeding budgeted amounts, disrupting production flow. This study employs a descriptive qualitative method oriented toward natural phenomena, utilizing a naturalistic approach through field studies. The results indicate that actual maintenance costs frequently exceed budgets, as seen in 2013 (IDR 600,000 overrun), 2014 (IDR 780,000), 2015 (IDR 1,400,000), and 2016 (IDR 410,000). Contributing factors include frequent machine breakdowns, spare parts price increases, and suboptimal routine maintenance. Production declines occurred due to machine failures disrupting manufacturing processes. Recommendations include establishing reserve budgets for price fluctuations, enhancing routine maintenance schedules, and employing competent accountants for more accurate budgeting.